Effects of palm-based edible coating on the postharvest life of guava (psidium guajava l.) and palm-based chitosan film on cherry tomato (solanum lycopersicum c.) / Ruzaina Ishak - Ishak, Ruzaina (Institute of Graduate Studies, UiTM, 2015)
This study was conducted to determine the potential of palm stearin (PS) as edible coating materials for fruits. The palm stearin was blended with 20-80% palm kernel olein (PKOo) and the properties of the blends were evaluated in terms of the slip melting point (SMP), solid fat content (SFC), fatty acid and triacylglycerol compositions (TAG), and polymorphism. Blending of PS with PKOo reduced the SMP, SFC, altered the FAC and TAG composition and changed the crystal polymorphism from β to mixture of β and β’. The changes in the physicochemical properties of PS were due to the replacement of the high melting TAG in PS with medium chain TAG in PKOo. From the analysis, 1:1 and 3:2 were the better PSPKOo blend formulations in slowing down the weight loss, respiration gases and gave better appearance when compared to other PSPKOo blends formulations. These two different coating formulations, 1:1 and 3:2 PSPKOo blends were applied onto guava by hand-wiping techniques, stored at 10°C and 20°C and were compared to beeswax (commercial coating) in terms of respiration gases, cohesiveness, weight loss, glossiness, colour and appearance. Guavas coated with 1:1 PSPKOo blend showed the lowest weight loss, while coating with 3:2 PSPKO showed the best guava appearance at 20°C. Both the PSPKOo coating blends significantly reduced (p<0.05) the weight loss, loss of O2 and CO2, glossiness, lightness, greenness and yellowness of guava stored at 20°C for 21 days when compared to beeswax. No significant difference (p>0.05) was observed between the two coating formulations in terms of weight loss, ethylene gas concentrations, lightness, greenness and yellowness of guava for both storage temperatures…